Spectroscopic investigation (FT-IR and FT-Raman), vibrational assignments, HOMO–LUMO analysis and molecular docking study of 1-hydroxy-4, 5, 8-tris(4-methoxyphenyl) anthraquinone. (December 2015) - Renjith, R.; Sheena Mary, Y.; Tresa Varghese, Hema; Yohannan Panicker, C.; Thiemann, Thies; Shereef, Anas; Al-Saadi, Abdulaziz A.
Abstract: FT-IR and FT-Raman spectra of 1-hydroxy-4, 5, 8-tris(4-methoxyphenyl)anthraquinone were recorded and analyzed. The vibrational wavenumbers were computed using DFT quantum chemical calculations. The data obtained from wavenumber calculations were used to assign the vibrational bands obtained experimentally. A detailed molecular picture of the title compound and its interactions were obtained from NBO analysis. From the MEP plot it is clear that the negative electrostatic potential regions are mainly localized over carbonyl group. There is some evidence of a region of negative electrostatic potential due to π-electron density of the benzo groups. Molecular docking study shows that methoxy groups attached to the phenyl rings and hydroxyl group are crucial for binding and the title compound might exhibit inhibitory activity against PI3K and may act as an anti-neoplastic agent. Graphical abstract: Highlights: Vibrational spectra, MEP, hyperpolarizability, NBO analysis were reported. The wavenumbers are calculated theoretically using Gaussian09 software. The geometrical parameters are in agreement with that of similar derivatives. Molecular docking is reported.